(3w+4)+5(w-2)-3(6w-8)=10

Simple and best practice solution for (3w+4)+5(w-2)-3(6w-8)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3w+4)+5(w-2)-3(6w-8)=10 equation:


Simplifying
(3w + 4) + 5(w + -2) + -3(6w + -8) = 10

Reorder the terms:
(4 + 3w) + 5(w + -2) + -3(6w + -8) = 10

Remove parenthesis around (4 + 3w)
4 + 3w + 5(w + -2) + -3(6w + -8) = 10

Reorder the terms:
4 + 3w + 5(-2 + w) + -3(6w + -8) = 10
4 + 3w + (-2 * 5 + w * 5) + -3(6w + -8) = 10
4 + 3w + (-10 + 5w) + -3(6w + -8) = 10

Reorder the terms:
4 + 3w + -10 + 5w + -3(-8 + 6w) = 10
4 + 3w + -10 + 5w + (-8 * -3 + 6w * -3) = 10
4 + 3w + -10 + 5w + (24 + -18w) = 10

Reorder the terms:
4 + -10 + 24 + 3w + 5w + -18w = 10

Combine like terms: 4 + -10 = -6
-6 + 24 + 3w + 5w + -18w = 10

Combine like terms: -6 + 24 = 18
18 + 3w + 5w + -18w = 10

Combine like terms: 3w + 5w = 8w
18 + 8w + -18w = 10

Combine like terms: 8w + -18w = -10w
18 + -10w = 10

Solving
18 + -10w = 10

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -10w = 10 + -18

Combine like terms: 18 + -18 = 0
0 + -10w = 10 + -18
-10w = 10 + -18

Combine like terms: 10 + -18 = -8
-10w = -8

Divide each side by '-10'.
w = 0.8

Simplifying
w = 0.8

See similar equations:

| 4x+224=136 | | 78x-474=0 | | 2a+3a+9= | | 8z^3-6z^2=72z-54 | | 4t+224=136 | | 3m^2+5m+7=0 | | 0.71=ln(y) | | 5(x+2)+5=15 | | 4.1a+9.98=-8.06 | | 2x+75=725 | | -(3w+4)+5(w+2)-3(6w-8)=10 | | 2x+69=819 | | 2(-5+2x)=x-1 | | (5y+8)(1+y)=0 | | b=y+ty | | -9=5+2y | | 3x^4-9x^3-1x^2=0 | | -335=-14x-125 | | (9-x)(9-x)=17 | | 166=2x-3(6x+18) | | 6x^2+14x-9x-21= | | 7r+4=2r+20 | | -4/9z=-3/5 | | 4x-9=5x+4 | | -48-14x=-202 | | 2ix^2+x+15i=0 | | 4.5=2x+3 | | 2x=429 | | 3-5n+3n=35-72 | | 5(x+7y)-8(6+y)= | | 60x^2+120x=0 | | -7+2x=9 |

Equations solver categories